Implementasi Pemupukan NPK pada Budidaya Labu Madu Hibrida - Nasehah, Durrotun; Juhan, Muhammad (JURNAL AGROPLANT, 2022)
One type of pumpkin that is still rarely cultivated by the Indonesian people is the honey gourd, while the honey gourd is rich in benefits that are good for health and the honey gourd has high economic value because it is still rarely cultivated. In addition, the relatively higher price of honey compared to other yellows makes this pumpkin a sufficient source of income for farmers. One of the efforts to meet the demand for honey pumpkin yields is to use the right dose of NPK fertilizer on honey pumpkin plants. The study used a randomized block design (RAK) with 6 doses of fertilization treatment, repeated 4 times. So the total experiment is 24 plants. The treatments used were R0 without chemical fertilizer, R1 at 20% dose of chemical fertilizer, R2 40% dose of chemical fertilizer, R3 60% dose of chemical fertilizer, R4 80% dose of chemical fertilizer and R5 100% dose of chemical fertilizer. The results showed that the fertilizer dose of 20% (R1) gave the best effect on the finished fruit to harvest and fruit weight. The dose of fertilization has no effect on the growth and size of plant organs.